1980
DOI: 10.1002/jclp.6120360221
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of alpha biofeedback therapy: Negative results

Abstract: Assessed the utility of alpha biofeedback training in the treatment of psychiatric patients (N = 66). Biofeedback and placebo biofeedback groups were given alpha or mock-alpha training sessions, and their improvement on 54 variables was compared to that of no-treatment controls. Only a chance number of significant differential changes appeared among the three groups. A comparison of these negative results with an earlier study from our laboratory that had yielded positive findings suggested that clinical impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
5
1
1
Order By: Relevance
“…The benefits in the current study may have derived from attention given with verbal instructions from the trainer (Watson & Herder, 1980), but such benefit was not shown in previous studies (Auerbach et al, 1992;Lutgendorf et al, 1997;McCain, Zeller, Cella, Urbanski, & Novak, 1996). It cannot be definitively confirmed that such attention did not lead to these results, but the attention from other measures has not led to such effects.…”
Section: Discussioncontrasting
confidence: 67%
“…The benefits in the current study may have derived from attention given with verbal instructions from the trainer (Watson & Herder, 1980), but such benefit was not shown in previous studies (Auerbach et al, 1992;Lutgendorf et al, 1997;McCain, Zeller, Cella, Urbanski, & Novak, 1996). It cannot be definitively confirmed that such attention did not lead to these results, but the attention from other measures has not led to such effects.…”
Section: Discussioncontrasting
confidence: 67%
“…This makes it difficult to determine which of the treatments was therapeutic. Similarly, workers in our laboratory found a wave biofeedback to be effective in the reduction of anxiety when it was combined with relaxation training, but not when it was administered alone (Passini et al, 1977;Watson & Herder, 1980). These reports raise questions about the efficacies of training in deep breathing and biofeedback for the treatment of PTSD and other anxiety disorders.…”
mentioning
confidence: 94%
“…Nonlearners remained unchanged mentally. Watson and Herder (1980) gave alphaenhancement contingent feedback to 22 patients, and noncontingent to the same number. Another 22 control patients got no treatment.…”
Section: Studies Of Patientsmentioning
confidence: 99%